2023
DOI: 10.15388/infedu.2023.29
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Evolution of Computational Thinking in Education: A Bibliometrics Analysis of Scopus Database from 1987 to 2023

Abstract: In today's world, the ability to think computationally is essential. The skillset expected of a computer scientist is no longer solely based on the old stereotype but also a crucial skill for adapting to the future. This perspective presents a new educational challenge for society. Everyone must have a positive attitude toward understanding and using these skills daily. One thousand two hundred seven documents about computational thinking (CT) may be found while searching the Scopus database from 1987 to 2023.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…In addition, the methodology of prototyping software applications involves knowing how to handle the processes of computational thinking (Melro et al, 2023) (Romero et al, 2017): abstraction, algorithmic thinking, automation, decomposition, debugging and generalization (Cansu & Cansu, 2019) (Rafiq et al, 2023) (Wing, 2008). It is thus demonstrated that problem solving processes, widely known in programming environments, are also applicable to the architectural discipline, being used to drive creativity and formal generation (Cannaerts, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the methodology of prototyping software applications involves knowing how to handle the processes of computational thinking (Melro et al, 2023) (Romero et al, 2017): abstraction, algorithmic thinking, automation, decomposition, debugging and generalization (Cansu & Cansu, 2019) (Rafiq et al, 2023) (Wing, 2008). It is thus demonstrated that problem solving processes, widely known in programming environments, are also applicable to the architectural discipline, being used to drive creativity and formal generation (Cannaerts, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is the pedagogical foundation of computational thinking (Wing, 2008) (Osio & Bailón, 2020). It is a problem-solving model that has sparked growing interest in the academic community, specially during the last decade (Rafiq et al, 2023), and is still the object of research, for which multiple definitions exist (Cansu & Cansu, 2019). According to Jeannette Wing (2011), CT "is the thought process involved in formulating problems and their solutions so that the solutions are represented in a form that can be effectively carried out by an information-processing agent."…”
Section: The Relationship Between Students and Computers: Curriculum ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies reveal how the use of technology can increase the level of creativity, innovation and design thinking in the next guiding question, allowing students to consider technologies that could be leveraged to work on the project more efficiently (Pacheco-Velázquez et al, 2023;Rafiq et al, 2023). This includes videos, tutorials, and self-study sites to gain a deeper understanding before solving a problem.…”
Section: Introductionmentioning
confidence: 99%